2017
DOI: 10.5650/jos.ess17097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fatty Acid Addition to Oil-in-water Emulsions Stabilized with Sucrose Fatty Acid Ester

Abstract: Adding fatty acids to an oil-in-water (O/W) emulsion changes the stability of the emulsion. In this study, we prepared a series of O/W emulsions consisting of oil (triolein/fatty acid mixture), water and a range of surfactants (sucrose fatty acid esters) with varying hydrophilic-lipophilic balance (HLB) in order to determine the effects of alkyl chain length and the degree of unsaturation of the fatty acid molecules on the stability of the emulsions. As a result, sucrose fatty acid esters with HLB = 5-7 were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…3), and no phase separation was observed in the formulation during storage at -4 ºC for 21 days, showing that silk protein could play an important role in the stability of the lipid particles from the conjunct of fatty acid esters. Watanabe (Watanabe et al 2018) showed that sucrose fatty acid esters with HLB = 5-7 were suitable for obtaining O/W emulsions. In addition, the creaming phenomenon was inhibited for 30 days or more when fatty acids with a linear saturated alkyl chain with 14 or more carbon atoms were added.…”
Section: Resultsmentioning
confidence: 99%
“…3), and no phase separation was observed in the formulation during storage at -4 ºC for 21 days, showing that silk protein could play an important role in the stability of the lipid particles from the conjunct of fatty acid esters. Watanabe (Watanabe et al 2018) showed that sucrose fatty acid esters with HLB = 5-7 were suitable for obtaining O/W emulsions. In addition, the creaming phenomenon was inhibited for 30 days or more when fatty acids with a linear saturated alkyl chain with 14 or more carbon atoms were added.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, different types of SEs were used to determine the effects of hydrophilic-lipophilic balance (HLB) values on the development of colloidal drug delivery systems. As the degree of sucrose esterification and fatty acid chain length increased, the HLB value of SE became decreased [ 35 ]. SE Laurate 1695 that has a high HLB value of 16 and was able to produce a large region of NE with small droplet size distribution and uniformity.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, sodium alginate’s properties have been used in chewing gum but not in extrusion [ 45 ]. New studies have shown that sodium alginate could be used in extrusion and could formulate microcapsules with essential oil as the core material [ 26 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The primary emulsions for microcapsules were prepared similarly in all studies [ 23 , 26 , 33 ], including this study. Yet in this research, three different methods were used for group 5 emulsions ( Figure 1 ) to determine which method is the most effective and results in the highest CI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation